2015
DOI: 10.1063/1.4936666
|View full text |Cite
|
Sign up to set email alerts
|

The influence of charged-induced variations in the local permittivity on the static and dynamic properties of polyelectrolyte solutions

Abstract: There is a large body of literature investigating the static and dynamic properties of polyelectrolytes due both to their widespread application in industrial processes and their ubiquitous presence in biology. Because of their highly charged nature, polyelectrolytes tend to alter the local dielectric permittivity of the solution within a few nanometers of their backbone. This effect has, however, been almost entirely ignored in both simulations and theoretical work. In this article, we apply our recently deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
(158 reference statements)
1
9
0
Order By: Relevance
“…Corresponding simulation findings for water molecules around charged and uncharged objects as well as around polyelectrolytes were observed in Refs. [26,[63][64][65][66]. All studies reveal significant ordering effects when compared to bulk phase due to the polarity of water molecules.…”
Section: Dielectric Decrement Effectsmentioning
confidence: 90%
See 3 more Smart Citations
“…Corresponding simulation findings for water molecules around charged and uncharged objects as well as around polyelectrolytes were observed in Refs. [26,[63][64][65][66]. All studies reveal significant ordering effects when compared to bulk phase due to the polarity of water molecules.…”
Section: Dielectric Decrement Effectsmentioning
confidence: 90%
“…Interestingly, although the corresponding expressions (Equation 18) can be used for further evaluation in mean field PB approaches, their occurrence can be solely attributed to specific molecular representations which are usually ignored. Recent experimental and simulation outcomes suggested that comparable effects also rationalize the dynamic properties of polyelectrolytes in presence of high salt concentrations [26,65,69]. Specifically the dielectric decrement effect and its influence on the polyelectrolyte in terms of dynamic properties like ionic conductivities attracted recent experimental and theoretical attention [26,65].…”
Section: Dielectric Decrement Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this simple view, it has to be mentioned that the value of the dielectric constant also depends on the chosen position, as it can locally change in close vicinity to ions, uncharged solutes, interfaces, and due to inhomogeneities in the solution [64,[110][111][112][113]. Moreover, it is also affected by solvent-solvent, solvent-ion, and ion-ion interactions, which contribute significantly to the net value of the dielectric constant.…”
Section: Dielectric Decrement Effectsmentioning
confidence: 99%